Indirect Language Learning Strategies in Academic Speaking Class - Anisa Nurul Amri (Universitas Nurul Jadid, 2026)
AbstractEffective communication in academic contexts requires not only linguistic proficiency but also the strategic use of learning approaches that support speaking performance. This study aimed to investigate the use of indirect strategies, namely metacognitive, affective, and social strategies among EFL students in a Speaking for Academic Purposes class at UIN Mahmud Yunus Batusangkar. A descriptive quantitative design with a cross-sectional survey was employed. The population consisted of 46 fifth-semester students of the English Teaching Department, selected through total sampling, with 45 valid respondents. Data were collected using a closed-ended questionnaire adapted from Oxford’s (1990) Strategy Inventory for Language Learning (SILL) with 55 items. The instrument was validated using Aiken’s V (0.77, valid) and showed high reliability (Cronbach’s Alpha = 0.975). Descriptive statistics were used for data analysis. The findings revealed that students “usually” employed indirect strategies in their academic speaking, with a high overall mean. Specifically, metacognitive strategies (M = 117.07), affective strategies (M = 49.29), and social strategies (M = 45.80) all fell within the “usually used” category. These results indicate that students actively planned, monitored, and evaluated their performance, regulated their emotions, and engaged in cooperative interactions. The study highlights the importance of integrating indirect strategies into EFL pedagogy to strengthen students’ academic speaking competence. Keywords: academic speaking, indirect learning strategies, metacognitive strategies, affective strategies, social strategies